Embodied Abstractions and Emotional Resonance in Chrétien's Chevalier de la Charrette - Fuksas, Anatole Pierre (Cognitive philology, 2011)
Novels typically (and necessarily) describe character-specific emotional responses to perceptual events or memories and emotional decisions which underly purposeful intentional actions. Accordingly, the study of emotions is crucial to the understanding of the integrated descriptive system that joins together perceptual events, emotional modulations and proper actions in a narrative whole which aims at working in the very same way the actual human experience of nature and society does. A study focusing on meaningful episodes of Chrétien de Troyes’ Chevalier de la Charrette (vv. 362-81; 1420-44; vv. 2732-39; 3047-54) aims at showing how recent advances in neuroscience make it possible to address novelistic descriptions of emotions in a way which contributes to explaining why novels are made the way they are and why the novelistic genre evolved into a global standard for storytelling.